spectroscopic stury of lewis bases coordinating to vanady - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
formation constants for the conrdination of aniline pyridine dimethyl sulfoxide dimethyl formamide ethanol dimethylamine have been determined the cordination